Potential distribution of eight species of Scolytinae and Platypodinae beetles (Coleoptera: Curculionidae) collected in native avocado orchards of Nuevo Leon, Mexico - Quiroz-González, Ian Humberto; Gutiérrez-Díez, Adriana; Equihua-Martínez, Armando; Ochoa-Ascencio, Salvador; Carballo-Méndez, Fernando de Jesús; Méndez-Zamora, Gerardo; Cerda-Hurtado, Ivón Montserrat (Revista Colombiana de Entomología, 2024)
The subfamilies Scolytinae and Platypodinae (Coleoptera: Curculionidae) include bark and ambrosial beetles considered threats in natural ecosystems and agricultural and forest crops due to their damage's ecological and economic impact. The distribution, population dynamics and diversity of the beetle species are affected by environmental factors, and ecosystem fragmentation. Based on the capture of eight beetle species from these subfamilies collected with multi-funnel tramps baited with ethanol in avocado orchards of Aramberri, Nuevo Leon, Mexico, was projected its potential geographic distribution in Mexico using the Maxent v.3.4.4 software. The identification of the captured beetles was done with taxonomic keys; a database was created with records of its presence in regions of Mexico, to model its distribution considering the climatic variables of greatest influence. The potential distribution maps generated, allow the prediction of these species in regions with optimal climatological conditions for their establishment; this information can be used to expand sampling areas, and implement preventive strategies against introducing exotic species. Araptus schwarzi, Monarthrum gracilior, Xyleborinus gracilis and Xyleborus horridus are new records of Scolytinae subfamily species to Nuevo Leon. Corthylus flagellifer, Euplatypus parallelus, Xyleborus ferrugineus, and Xyleborus volvulus are ambrosia beetle species that should be closely monitored in Mexico since they can be potential sources of dissemination of their symbiont phytopathogenic fungi.